Identification of Scientific Knowledge of the Patehan Tradition of Yogyakarta Palace as a Source of Natural Science Learning - Larassati, Annasya Sakha Alika; Suciati*, Suciati; Sari, Meida Wulan; Silvita, Silvita; Prasetyo, Opik; Rachman, Hening Triandika (Jurnal Pendidikan Sains Indonesia, 2025)
The integration of local wisdom into science learning faces challenges due to the focus on theoretical understanding rather than real-world applications. Teachers often overlook the potential of local wisdom in science education, and the process of incorporating cultural phenomena as scientific learning topics is perceived as complex. This study aims to identify the scientific knowledge embedded in the "Patehan" tradition of the Yogyakarta Palace. The research follows a qualitative ethnographic approach with a sample of five respondents selected via purposive sampling from the Patehan servants. Data collection involved interviews, observations, and documentation, with internal validation for data accuracy. Data analysis was carried out interactively through three stages: data reduction, data presentation, and conclusion drawing. The results indicate that the "Patehan" tradition contains scientific knowledge across four main aspects: biology, physics, chemistry, and earth and space sciences. These findings highlight the potential of local wisdom, such as the "Patehan" tradition, to enhance students' understanding of science concepts